2008
DOI: 10.1037/0893-164x.22.3.402
|View full text |Cite
|
Sign up to set email alerts
|

Personality and performance-based measures in the prediction of alcohol use.

Abstract: Research has demonstrated a variable relationship between alcohol consumption and self-report personality measures of novelty seeking and harm avoidance. Research has also demonstrated a relationship between performance-based measures of risk taking and substance use. The current study compared the utility of personality measures and performance-based measures in the prediction of alcohol use. The authors hypothesized that the domains would contribute uniquely and would also interact in the prediction of alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 36 publications
4
51
1
1
Order By: Relevance
“…These results align with several studies revealing no significant correlation between BART outcomes and trait sensation seeking and impulsivity measures (Aklin et al, 2005;Hunt et al, 2005;Lejuez et al, 2003a;Skeel et al, 2008). The majority of the literature points toward weak associations between psychometric and behavioral impulsivity measures among nonclinical samples, suggesting that the behavioral tendencies identified in self-report and laboratory measures may differ (Lane et al, 2003;Reynolds et al, 2006aReynolds et al, , 2008.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These results align with several studies revealing no significant correlation between BART outcomes and trait sensation seeking and impulsivity measures (Aklin et al, 2005;Hunt et al, 2005;Lejuez et al, 2003a;Skeel et al, 2008). The majority of the literature points toward weak associations between psychometric and behavioral impulsivity measures among nonclinical samples, suggesting that the behavioral tendencies identified in self-report and laboratory measures may differ (Lane et al, 2003;Reynolds et al, 2006aReynolds et al, , 2008.…”
Section: Discussionsupporting
confidence: 76%
“…Unlike other behavioral measures, the BART conceptualizes risk-taking as occurring on a continuum, with risk-taking becoming disadvantageous only at a certain point, which varies according to the circumstances (Lejuez et al, 2003a). Thus, the BART is advised for administration in nonclinical populations, as it captures risky behavior that is not necessarily disadvantageous (Skeel et al, 2008). However, despite significant correlations with selfreported real-world substance use behaviors (Aklin et al, 2005;Lejuez et al, 2003a,b), the BART has not consistently detected the acute effects of drugs on risk-taking.…”
Section: Discussionmentioning
confidence: 99%
“…Fernie, Cole, Goudie, and Field (2010) reported that BART performance significantly predicted alcohol use after controlling for gender differences and trait impulsivity. This finding represents an extension of the findings of Skeel, Pilarski, Pytlak, and Neudecker (2008) who suggested that while BART performance alone did not predict alcohol use, an interaction between BART performance and novelty seeking as measured by the Tridimensional Personality Questionnaire explained variance in reported alcohol consumption (i.e., poorer BART performance was associated with greater alcohol use as novelty seeking increased, and better BART performance was associated with greater alcohol use as novelty seeking decreased). Fecteau et al (2007) employed the BART to demonstrate that by increasing neuronal excitation in the dorsolateral PFC with transcranial direct current stimulation, healthy participants responded more conservatively.…”
mentioning
confidence: 53%
“…With regard to the temperament dimensions, there is some evidence to suggest that novelty seeking (positively) and harm avoidance (negatively) are related to alcohol use (Koposov, Ruchkin, Eisemann, and Sidorov, 2005;Skeel, Pilarski, Pytlak, and Neudecker, 2008). Of the character dimensions, both cooperativeness and selfdirectness may be related to alcohol use (Egger et al, 2007).…”
Section: Seven-factor Measuresmentioning
confidence: 99%